Analisis Geometri Peledakan Terhadap Fragmentasi Hasil Peledakan pada PT. Diamond Alfa Propertindo Kecamatan Mawasangka Tengah Kabupaten Buton Tengah Provinsi Sulawesi Tenggara - Marina, Marina; Salu, Sahrul Poalahi; Dzakir, La Ode (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2024)
ABSTRACT PT. Diamond Alfa Propertindo is a company operating in the mining sector located in Gundu-gundu Village, Central Mawasangka District, Central Buton Regency, Southeast Sulawesi Province, with an area of 4,905 Ha. Where the research location is located in Pit Mr. Cheng. Where the results of geometric calculations based on R.L Ash's theory are Burden (B) 2 meters, Spacing (S) 3 meters, Stemming (T) 2 meters, Length of filled column (PC) 4 meters, Depth of blast hole (H) 6 meters, Subdrilling ( J) 0.4 meters, and ladder height (L) 5.6 meters, resulting in production of 6,609.6 bcm/blast. The geometric results in the field are burden 2,9 meters, spacing 2,91 meters, stemming 0,78 meters, depth of blast hole 3,58 meters, Subdrilling is not used in the field so it is called a Quarry floor, Fill column length is 2,8 meters, resulting in a production of 3,099.11 bcm/blast with the amount of Anfo used being 16,32 kg, resulting in an average fragmentation size for 10 blasts of 22,25 cm with rock passing using the Kuz-ram model of 53,51%. Meanwhile, based on the Split Desktop 2.0 software, it produces an average fragmentation size of 22,71 cm with 80% rock escap e.